The bag boutique : 20 bright and beautiful bags to sew - Grabler-Crozier, Debbie von (Search Press, 2018)
Add a gorgeous finishing touch to any outfit! This mouthwateringly colourful book contains 20 beautiful bags to sew from popular designer Debbie von Grabler-Crozier. It includes a huge variety of different styles and sizes, from totes and bucket bags to backpacks, clutches and shoulder bags, and Debbie makes each one easy. The book contains a complete guide to all the techniques needed, shown using easy-to-follow step-by-step photography. Also included is a section on creating beautiful finishing touches, including embroidery, applique, crocheted flowers, beaded charms and labelling. All the templates required are included on a handy pull-out sheet.